2012
DOI: 10.1016/j.aap.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Distraction and pedestrian safety: How talking on the phone, texting, and listening to music impact crossing the street

Abstract: As use of handheld multimedia devices has exploded globally, safety experts have begun to consider the impact of distraction while talking, text-messaging, or listening to music on traffic safety. This study was designed to test how talking on the phone, texting, and listening to music may influence pedestrian safety. 138 college students crossed an interactive, semi-immersive virtual pedestrian street. They were randomly assigned to one of four groups: crossing while talking on the phone, crossing while texti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
203
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(219 citation statements)
references
References 23 publications
15
203
1
Order By: Relevance
“…Pedestrian use of mobile phones increases cognitive distraction, decreases the ability to react to sudden changes, and increases disturbing actions causing injury or even death [3][4][5][6]. For example, in a virtual experiment, it was shown that texting while walking increases the chance of being hit by a car or a motorcycle; moreover, texting is a distraction from the surroundings [7]. Previous research on texting while walking has shown that pedestrians walk slower with less traffic awareness [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pedestrian use of mobile phones increases cognitive distraction, decreases the ability to react to sudden changes, and increases disturbing actions causing injury or even death [3][4][5][6]. For example, in a virtual experiment, it was shown that texting while walking increases the chance of being hit by a car or a motorcycle; moreover, texting is a distraction from the surroundings [7]. Previous research on texting while walking has shown that pedestrians walk slower with less traffic awareness [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Gait change with regard to mobile phone use threatens pedestrian safety [10]. When crossing the street, individuals texting on a mobile phone are more likely to be struck by a car than those with high concentration [5]. In the practical study of Schabrun et al [2] 35% of subjects had experienced an accident during mobile phone use, and 83% of the subjects in our study had an increased risk of accident resulting from mobile phone use.…”
Section: Discussionmentioning
confidence: 71%
“…Previously, there were many concerns about the risk of using mobile phones during driving. However, concerns on the risk of using mobile phones during walking have increased recently [4,5]. For example, pedestrian accidents related to mobile phone use have increased since 2006 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign experts have made in-depth studies on pedestrian distraction [1][2][3][4][5][6], at the same time, they have made studies on different groups of people. The main research idea is to select the research object in the way of random sampling, then to further understand the walking habits, gender, age, race and so on of the research object, and carry out training on experiment courses.…”
Section: Introductionmentioning
confidence: 99%